Meanings of visually impaired university student about services to support in higher education during the pandemic (Research, Society and Development, 2022)
This article aims to apprehend the meanings of university students with visual impairments about the university’s inclusion support services, especially in the context of remote teaching.  Its theoretical-methological foundation is Dialectical Historical Materialism and Socio-Historical Psychology. Participants in this research were 6 university students with visual impairments, from different courses at a federal university in northeastern Brazil. For data production, a semi-structured interview and a reflective session were used. For data analysis, the procedure of meaning cores was used. The meanings apprehended showed the existence of bureaucratized processes to request institutional support services; the impotence of the accessibility nucleus, which did not meet the demands presented by the university students, especially the pedagogical ones; as well as the pedagogical fragility for the development of the inclusive academic process. With this, it was possible to conclude that the determinations experienced by the university students constituted negative meanings about the inclusion support services.